2013
DOI: 10.3126/njst.v14i1.8874
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fresh or Cryopreserved Pollen on Seed Setting of Intervarietal and Interspecific Crosses of Gladiolus

Abstract: An experiment was conducted in the field of Indian Institute of Hortricultural Research, Hessaraghatta, Bangalore during August 2006 to June 2008. The experiment consisting of eight treatment combinations were laid out in '2x4' factorial RCBD with 5 replications to assess seed set per capsule. The results revealed that highly significant differences were observed for number of well-developed seeds and underdeveloped seeds. Among four cross combinations 'H.S. 88-10-22 x Shobha' (27.63 well-developed seeds per c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…The variation in number of florets opened per spike might be attributed to the differential numbers of florets per spike and accumulation of carbohydrates due to varied leaf production in turn, variation in these aspects might be due to genetic make-up of the plants (Shakya 2006). Varietal variation in number of florets per spike was also reported by (Sindhu and Verma 1995), (Regmi 2000) and (Poon 2009). The plant height, spike length and rachis length also varied enormously among the genotypes which might be due to differences in size of corms i.e., largest corms produced tallest plant with high spike and rachis length while smallest sized corms produced the plants with the shortest height with short spike and rachis length.…”
Section: Discussionsupporting
confidence: 58%
“…The variation in number of florets opened per spike might be attributed to the differential numbers of florets per spike and accumulation of carbohydrates due to varied leaf production in turn, variation in these aspects might be due to genetic make-up of the plants (Shakya 2006). Varietal variation in number of florets per spike was also reported by (Sindhu and Verma 1995), (Regmi 2000) and (Poon 2009). The plant height, spike length and rachis length also varied enormously among the genotypes which might be due to differences in size of corms i.e., largest corms produced tallest plant with high spike and rachis length while smallest sized corms produced the plants with the shortest height with short spike and rachis length.…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, relatively high number of developed seeds (55.9 per capsule) was recorded from the crosses between 'Psittacinus hybrid and G-4 in the similar study under Dailekh condition, Nepal when crosses were made from the first fortnight of April to the first fortnight of May. The findings of the two studies formerly made by Dhaduk et al (1987) and Poon (2009) are quite different from that of the recent study most presumably due to the inclusion of different genotypes as male parents in crosses, some of flower abortions at low temperature and low light intensity during early January and mid February (12.0 0 -29.0 0 C) under Bengluru environments, India. Moderate high temperature (15 0 -32 0 C) during April and May possibly could produce a positive effect in overcoming incongruity in interspecific crosses of gladiolus under mid-hill environments of Dailekh, Nepal.…”
Section: Performances Of Ten Interspecific Cross Combinationsmentioning
confidence: 64%
“…Dhaduk et al (1987) reported that varieties viz., 'Sylvia','Psittacinus hybrid', Jogenaar' did not set capsule at all under natural self pollination, and 'Psittacinus hybrid x Sancerre' produced the low number of seed per capsule (0.38) under artificial cross pollination. Poon (2009) recorded the high number of developed seeds (15.22 per capsule) from the crosses between 'Psittacinus hybrid and Kum Kum' under Bengaluru condition, India when crosses were made from early January to mid February. Moreover, relatively high number of developed seeds (55.9 per capsule) was recorded from the crosses between 'Psittacinus hybrid and G-4 in the similar study under Dailekh condition, Nepal when crosses were made from the first fortnight of April to the first fortnight of May.…”
Section: Performances Of Ten Interspecific Cross Combinationsmentioning
confidence: 99%
See 1 more Smart Citation